2002
DOI: 10.1103/physrevc.66.014308
|View full text |Cite
|
Sign up to set email alerts
|

Tilted dipole bands in123Xe

Abstract: High-spin states in 123 Xe were populated in the 110 Pd( 18 O,5n) reaction at 75 MeV and gamma-ray coincidences were measured with the GASP spectrometer. A new rotational sequence of enhanced dipole transitions was established. This band, as well as a similar band in 124 Xe, may be described within the framework of the tilted axis cranking model as bands for which comparable amounts of angular momentum are generated by magnetic and collective rotation, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…4 from Ref. [7]). In this Comment we show that also the absolute B (M1) and B(E2) values are reproduced as well.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…4 from Ref. [7]). In this Comment we show that also the absolute B (M1) and B(E2) values are reproduced as well.…”
mentioning
confidence: 96%
“…In the first scenario [1][2][3] these bands are considered as collective bands built on 4qp excitations in which the angular momentum is generated predominantly by the collective rotation of the deformed core. The other scenario involves the shears mechanism [4], which is thought to play an important role in the structure of these bands [5][6][7]. Here the shears mechanism, which has originally been suggested in order to explain the angular momentum generation in nearly spherical nuclei, occurs on a deformed core, forming the so-called magnetic rotational bands of intermediate nature [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The level scheme of 124 Xe was investigated in previous studies and collective bands were established up to spin I ∼ 20 -30 [3,[16][17][18][19][20]. An extensive level scheme up to I ∼ 35 with several new rotational bands and noncollective terminating states was reported by Al-Khatib et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…G. Rainovski et al [10] had shown that comparable amounts of angular momentum were generated by the shears mechanism and collective rotation in 124 Xe, for which the deformation parameters are 2 ∼ 0.19 and γ ∼ 30 • . J. Cederkäll et al [11] have deduced the quadrupole moment, Q 0 = 2.7 e b, for the πg 9/2 −1 ⊗ νh 11/2 band in 108 Sb, from the Total Routhian Surfaces (TRS) calculations.…”
mentioning
confidence: 99%